El “aura” en la tragedia griega del Nacimiento - Miranda, Henry (2022)
Within the limits of Walter Benjamin’s The work of art in the age of mechanical reproduction and Friedrich Nietzsche’s The birth of tragedy, this essay will investigate the intersection between the concept of aura and the attic greek tragedy as conceived by Nietzsche. We will find that the concept of aura cannot account for the greek tragedy, because, the latter, instead of being experimented as something distant, is lived and described as an immersion, that, despite everything, still keeps its cult value. This work will answer the following - first what is aura; second, how does Nietzsche understand greek tragedy; and finally, what happens in the aura-tragedy crossing.